Antifungal efficacy of kenaf seed peptides mixture in cheese, safety assessment and unravelling its action mechanism against food spoilage fungi - Arulrajah, Brisha; Qoms, Mohammed S.; Muhialdin, Belal J.; Zarei, Mohammad; Hussin, Anis Shobirin Meor; Hasan, Hanan; Chau, De-Ming; Ramasamy, Rajesh; Saari, Nazamid (Elsevier, 2023)
This study investigated the preservation efficacy of kenaf seed peptides mixture (KSPM) in extending the shelf-life of cream cheese matrix and the effect on its physicochemical properties. Also, the safety of KSPM towards mammalian cells and the underlying fungicidal mode of action in-vitro and in-silico were assessed. The KSPM at 500 and 1000 mg/kg effectively prolonged the shelf-life of cream cheese for up to 11–21 days when stored at 25 °C and 4 °C, and significantly reduced the inoculated conidia counts by ∼3 log10 conidia/g. The safety assessment showed that KSPM maintained the proliferation of normal cell lines up to 30 mg/mL. The cell surface potential energy and hydrophobicity of fungi were altered due to the potent interactions between the peptides and the cell envelope, with KSPM causing significant fungal cell wall permeability and subsequent disruption of the cytoplasmic membrane integrity. KSPM treatment induced morphological destruction of conidia and mycelium and caused a significant loss of fungal cellular materials including K+, sugar, protein and nucleic acids (DNA and RNA), indicating irreversible damage to the fungal cytoplasmic membrane. The in-silico molecular docking study revealed that the peptides mixture efficiently interacted with fungal mannoprotein via the formation of hydrogen bonding, electrostatic interactions and hydrophobic forces. The molecular dynamics simulation showed that the peptide KPTGMR was tightly embedded into the fungal phospholipid bilayer membrane and inserted into the phosphate head groups which led to the formation of gaps, suggesting a transmembrane pore or channel action mechanism.